The Moderating Role Of Hostility In The Relationship Between Enriched Jobs And Health - Dwyer, Deborah J.; Fox, Marilyn L. (Academy of Management Journal, 2000)
The purpose of this study was to assess the proposed moderating role of one individual-level health risk factor?hostility?in the relationship between job enrichment and health care costs for a sample of nurses. The authors' findings indicate that hostility does moderate the relationship between job enrichment and health care costs; however, those who have more control in their jobs have fewer health problems, even when they demonstrate more hostility.